The didactic utilization of the Bible and Midrash in the plays of Zalman Aaron Lison - Yannay, Tony (Kaplan Centre for Jewish Studies, 2023)
Being a teacher in primary schools for many years made me aware of the power of dramatization as a didactic device. Then I came across Dr. Reisenberger's research project and preservation of all Hebrew Literature written in South Africa, and so I became familiar with the Hebrew plays of Zalman Aaron Uson. These plays were published between 1944 and 1951 in "Barkaal', which was the only Hebrew journal that was published in South Africa at that time. Notwithstanding the fact that Barkaals readership was primarily adults, the plays' target audience was Jewish children in the higher classes of primary school. (early teens). I then discovered that Zalman Aaron Uson was a teacher who taught Jewish studies to South African Jewish children in government primary schools. He wrote the plays in order to familiarize the children with various biblical narratives that he believed had to be taught. The idea behind the dramatization was not only to impart knowledge of the characters and events, but also to force the children to memorize the plays, which are in Hebrew; thus, providing the pupils with knowledge of their Religious Tradition and linguistic Heritage in a vibrant, endearing and effective way. This thesis highlights Lison's inimitable way of selection and utilization of Bible and Midrash as a didactic tool. It sets out the power of literature in general, and drama, as means to induce empathy and identification. This is followed by a detailed literary analysis of the plays with particular attention to the tracing of the Midrash from which Uson drew the dramatic details, the backdrop sets, names of secondary characters etc. The effectiveness of Lison's method is verified through the interviews with his past students, who are currently mature adults. A special note has to be added regarding the use of archival material - from Lison's bequest that the family so kindly allowed access to, as well as semistructured qualitative interviews with Lison's son, Dr. Michael Uson, and two of Lison's past students, who currently live in Israel. All the above concurred my hypothesis of the effectiveness of Lison's method and points out to his exceptional educational astuteness. The thesis includes copies of the plays in the appendix. The language utilized is Hebrew